2019
DOI: 10.3390/biom9060217
|View full text |Cite
|
Sign up to set email alerts
|

Role of the COP9 Signalosome (CSN) in Cardiovascular Diseases

Abstract: The constitutive photomorphogenesis 9 (COP9) signalosome (CSN) is an evolutionarily conserved multi-protein complex, consisting of eight subunits termed CSN1-CSN8. The main biochemical function of the CSN is the control of protein degradation via the ubiquitin-proteasome-system through regulation of cullin-RING E3-ligase (CRL) activity by deNEDDylation of cullins, but the CSN also serves as a docking platform for signaling proteins. The catalytic deNEDDylase (isopeptidase) activity of the complex is executed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 221 publications
(296 reference statements)
1
22
0
Order By: Relevance
“…In line with previous report, JAB1 potent protective activities in CVDs (Milic et al, 2019; Schwarz et al, 2017). Similarly, we discovered that the protein JAB1 could increase ABCA1 activity and promote cholesterol efflux; thus, preventing the formation oxLDL‐induced foam cells.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous report, JAB1 potent protective activities in CVDs (Milic et al, 2019; Schwarz et al, 2017). Similarly, we discovered that the protein JAB1 could increase ABCA1 activity and promote cholesterol efflux; thus, preventing the formation oxLDL‐induced foam cells.…”
Section: Discussionsupporting
confidence: 92%
“…HIF-1α is a short-lived protein and is ubiquitinated and degraded through the von Hippel-Lindau protein (pVHL)-E3 ubiquitin ligase pathway at normoxia [2]. CSN is reportedly associated with deubiquitination activity [6]. The ubiquitination assay showed that CSN8 overexpression could decrease HIF-1α ubiquitination (Fig.…”
Section: Csn8 Is Essential For Inducing Emt and Dormancy Under Hypoximentioning
confidence: 97%
“…The COP9 signalosome (CSN) is an evolutionarily conserved protein complex composed of 8 subunits (CSN1-CSN8) in higher eukaryotes, and plays an important role in ubiquitin-mediated protein degradation [6]. Previous reports indicated that the subunit of CSN, such as CSN6, is involved the malignant process of cancer [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The name COP9 signalosome, abbreviated as CSN, was eventually adopted to incorporate both the plant and human name, with the eight CSN subunits named CSN1 to CSN8 based on descending molecular weight. CSN mediates many fundamental and disease aspects of life, including, among others, cell cycle control, DNA repair, stemness, development, cancer and cardiovascular diseases [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%